Substantial control strategies of DFIG wind power system during grid transient faults - Le, H.; Islam, Syed (2008)
This paper discusses dynamic model of DFIG wind generator and improvement of controllers for better interaction between wind farm and power system during transient grid fault events. The improvements include Controller Implementation of Blade Pitch Angle, Frequency Stabilizer, Drive Train Stabilizer and STATCOM operation of the Grid Side Converter. ©2008 IEEE.